Heavy metal tolerance and polychlorinated biphenyl oxidation in bacterial communities inhabiting the Pasvik River and the Varanger Fjord area (Arctic Norway). (April 2019) - Rappazzo, Alessandro Ciro; Papale, Maria; Rizzo, Carmen; Conte, Antonella; Giannarelli, Stefania; Onor, Massimo; Abete, Carlo; Cefali, Pietro; De Domenico, Emilio; Michaud, Luigi; Lo Giudice, Angelina
Abstract: Heavy metals (HMs) and polychlorobiphenyls (PCBs) enter the Arctic environment through a variety of anthropogenic sources with deleterious effects towards biota and public health. Bacteria first transfer toxic compounds to higher trophic levels and, due to the tight link existing between prokaryotic community functions and the type and concentration of contaminants, they may be useful indicator of pollution events and potential toxicity to other forms of life. The occurrence and abundance of HM-tolerant and PCB-oxidizing bacteria in the sub-Arctic Pasvik river area, heavily impacted by anthropogenic modifications, was related to HM and PCB contamination. This latter more likely derived from local inputs rather than a global contamination with higher PCB and HM amounts (and higher bacterial viable counts) that were determined in inner and middle sections of the River. Finally, a panel of bacteria with potential applications in the bioremediation of cold environments were selected and phylogenetically identified. Graphical abstract: Unlabelled Image Highlights: The Pasvik River was contaminated by heavy metals and polychlorobiphenyls. Bacterial heavy metal tolerance was in the order Cu>Zn>Cd>Hg. Bacterial viable counts were higher in highest contaminated samples. Bacteria may be used as bioindicators of human impact in Arctic areas. Bacteria could be exploited in the bioremediation of contaminated cold areas.